Determinants and impact of bank financing on the economic and non-economic performance of SMEs in Bangladesh - Akther, Nafiza (2020)
Small and Medium Enterprises (SMEs) are seen as the most important drivers of country economic. Lack of capital will affect the contributions of SMEs to economic development. Thereby, bank financing may help SMEs in getting more funds to expand their business. However, some SMEs do not believe that this type of financing can help to improve their businesses. Hence, this study aims to identify the determinant factors of SMEs‟ bank financing. This study also examines the impact of bank financing on SMEs' economic and non-economic performances in Bangladesh. In pursuit of these objectives, this study adopts a quantitative method by distributing 403 questionnaires to the SMEs in Bangladesh. The data are collected explicitly from the owners and managers based on the availability and easy access to the SMEs. In doing so, this study uses a non-probability sampling technique. Besides, the Statistical Package for the Social Sciences (SPSS) is used to run the analysis. Furthermore, the Pecking Order Theory and Agency Theory are applied to support the study's proposed relationships between variables and hypotheses. The results of this study show that all the hypotheses are supported. The first seven hypotheses are developed under hypothesis one, revealing a significant relationship between determinants and bank financing. It indicates that SMEs take into account both internal and external factors during decisions on bank financing. Moreover, the results of hypotheses two and three are also supported and reveal that bank financing has a positive impact on SMEs' economic and non-economic performances in Bangladesh. The study has significant theoretical and contextual contributions and implications on the banks' governing authorities, the central bank's financial policymakers, and SMEs. Conclusively, the findings also provide a series of guidelines to the SMEs in Bangladesh regarding on the determinant factors and considerations for availing bank financing.